Evaluation of Islamic Education: Religiosity and Character Transformation in the Digital Era - Achmad Amir; Syarifuddin Ondeng; Afifuddin A (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article examines the evaluation of Islamic Religious Education (PAI) in the perspective of religiosity and character transformation in the digital era. Using a systematic literature review approach, this paper analyzes in depth the classical philosophical foundations of PAI evaluation drawn from the thought of Al-Ghazali and Ibn Khaldun, the nature of evaluation as an instrument for internalizing Islamic values, holistic and integrative evaluation principles, and the evolution of evaluation techniques from traditional methods to digital platforms based on learning analytics. This research also examines the strategic position and function of teachers as moral authorities amid the influx of artificial intelligence in contemporary educational evaluation systems. The findings indicate that comprehensive PAI evaluation must be capable of measuring cognitive, affective, and psychomotor dimensions in a balanced and proportional manner, while maintaining the spiritual essence and moral authority of teachers as irreplaceable spiritual guides. The use of technologies such as Learning Management Systems (LMS), multimodal-based digital portfolios, reflective journals as digital muhasabah media, and big data analytics provides new opportunities for personalized learning. However, the implementation of these technologies must always be balanced with a strict ethical approach, student privacy protection, and ecosystem synergy involving schools, families, and communities. These findings affirm that the success of PAI evaluation in the digital era is not solely determined by the sophistication of the technology used, but by the ability of educational institutions and their educators to balance digital innovation with Islamic spiritual values and the aspiration of forming the insan kamil as the highest goal of Islamic education.